2015
DOI: 10.1016/j.pbb.2015.02.022
|View full text |Cite
|
Sign up to set email alerts
|

The mixed-action delta/mu opioid agonist MMP-2200 does not produce conditioned place preference but does maintain drug self-administration in rats, and induces in vitro markers of tolerance and dependence

Abstract: Previous work in our laboratories provides preclinical evidence that mixed-action delta/mu receptor glycopeptides have equivalent efficacy for treating pain with reduced side effect profiles compared to widely used mu agonist analgesics such as morphine. This study evaluated the rewarding and reinforcing effects of a lead candidate, mixed-action delta/mu agonist MMP-2200, using a conditioned place preference assay as well as a drug self-administration procedure in rats. In place conditioning studies, rats unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Although the similar withdrawal-like naltrexone-elicited effects on food-maintained responding were unexpected, it remains the case that dependence on M6S may have developed more slowly with M6S than with morphine. In that regard, similar results have been observed with a mixed l/d opioid glycopeptide, 37,47 where it was suggested that heterodimerization of l/d opioid receptors (modulating neuronal network effects of l-and d-containing neurons at a level above the individual receptor) or additional cellular regulators in neurons could modulate the induction of tolerance and dependence at the receptor level, slowing tolerance development. Indeed, it has been previously reported that drugs with affinity for l and j opioid receptors demonstrated different results across tests of thermal nociception, schedule-controlled responding and drug self-administration, and our previous and present reports with the mixed l/d opioid agonist M6S contributes to this growing body of literature demonstrating that novel drug-receptor interactions may elicit distinct effects across experimental endpoints (e.g.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Although the similar withdrawal-like naltrexone-elicited effects on food-maintained responding were unexpected, it remains the case that dependence on M6S may have developed more slowly with M6S than with morphine. In that regard, similar results have been observed with a mixed l/d opioid glycopeptide, 37,47 where it was suggested that heterodimerization of l/d opioid receptors (modulating neuronal network effects of l-and d-containing neurons at a level above the individual receptor) or additional cellular regulators in neurons could modulate the induction of tolerance and dependence at the receptor level, slowing tolerance development. Indeed, it has been previously reported that drugs with affinity for l and j opioid receptors demonstrated different results across tests of thermal nociception, schedule-controlled responding and drug self-administration, and our previous and present reports with the mixed l/d opioid agonist M6S contributes to this growing body of literature demonstrating that novel drug-receptor interactions may elicit distinct effects across experimental endpoints (e.g.…”
Section: Discussionsupporting
confidence: 74%
“…One common adverse effect limiting the chronic use of μ opioid agonists is their notorious liability for abuse, physical dependence, and addiction . Prescription μ opioids are not only abused, but are also responsible for severe morbidity and death from overdose . The present report provides an initial characterization of the morphine‐like discriminative stimulus effects and physical dependence properties of the novel mixed‐action μ/δ opioid M6S in rats.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Accordingly, much effort has been dedicated to the development of new MOR agonists retaining potent analgesic effects, while mitigating or eliminating the deleterious side effects of the agents currently in use. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have investigated the pathways correlated with tolerance mechanisms in these receptors, especially in the face of morphine. Activation of β-arrestin-2, ERK1/2, and phosphorylated counterpart of ERK1/2 proteins was proved to be the most signaling pathways leading to µ-receptor downregulation and nally, drug dependence and antinociceptive tolerance [6][7][8].…”
Section: Introductionmentioning
confidence: 99%